KELAYAKAN FLIPBOOK KEANEKARAGAMAN ZOOPLANKTON DI SUNGAI AMBAWANG DALAM SUBMATERI PENCEMARAN AIR KELAS X SMA - Fazry, Nur; Hardigaluh, Basuki; Chandramila, Wolly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the feasibility of flipbook on the Sub-material of Water Pollution based on the zooplankton quality in Ambawang River, West Kalimantan. This research was quantitative with descriptive method. In this study, the validity of the flipbook media was done by validity test. Data validation results of the media will be analyzed using the analysis method of Content Validity Ratio (CVR). Based on the CVR value, the CVI (Content Validity Index) value was calculated for the overall assessment of the instrument items that have good content validity. CVI calculation result showed the overall criteria obtained have he CVI value of 0.95, which showed that the flipbook media on Sub-material of Water Pollution in the first grade of SMA was not feasible to be used as a learning medium. The use of flipbooks in the learning of Sub-material of Water PollutionÂ must be revisedÂ especially on the invalid item, namely adjusting the color variations to improve the attractiveness aspect.Â Keywords: Ambawang River, Flipbook media, Zooplankton, Water Pollution Sub-material